STRATEGI PEMASARAN UMKM ROTI DALAM MENINGKATKAN VOLUME PENJUALAN (STUDI KASUS ANNISA BAKERY LERPAK) - Ahmad, Ahmad (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
A business, whether small business or large business, requires a strategy to develop its business so that it continues to run on target. The implementation of a marketing strategy is very important for the company, this is due to the application of an appropriate and effective strategy. Annisa Bakery Lerpak is an MSME that produces various bakery products. The purpose of this research is to find out Annisa Bakery's marketing strategy in increasing sales volume. This research uses qualitative methods. And uses a random sampling technique where every member of the population has the same opportunity to be sampled. The research instruments were observation, interviews and documentation. The data analysis method in this research is descriptive qualitative. From the results Based on the observation of the researcher, it can be concluded that to be able to increase sales volume so that Annisa Bakery's bread can sell well in the market, namely by using the 4P marketing mix (Product, Price, Promotion and Place). One of the efforts made by Annisa Bakery is: Maintaining the quality of the bread, increasing the amount of production bread,as well as efforts to add production equipment.